Seismic Analysis of Flat Slab Structure Using ETABS Software : A Review - Mahobe, Rajat; Grover, R. K. (International Journal of Scientific Research in Civil Engineering, 2022)
The behavior of reinforced concrete moment resisting frame structures in recent earthquakes all over the world has highlighted the consequences of poor performance of beam column joints. Large amount of research carried out to understand the complex mechanisms and safe behavior of beam column joints has gone into code recommendations. The design of reinforced concrete structures solely depends on various parameters like bending moment; shear force and stress induced in a particular member of a structure. Variation in the magnitude of these parameters may alter the entire design of a particular element. In this paper we are presenting review of literature related to analysis of structures considering diaphragm effect.